Intel's official guide to 386 computing. - Edelhart, Michael (Berkeley, USA : Osborne McGraw-Hill, 1991)
"Now that you have your 386™ microprocessor-based PC, you'll want to learn how to take full advantage of its features to get the most from your investment. Intel's Official Guide to 386™ Computing is the book to choose for • Enhancing your 386 computer for maximum power. • Turning a 286 PC into a 386 PC. • Getting the most from Microsoft® Windows 3.0 and UNIX® on your 386 PC. • Making every application program run better and easier with the 386 chip. Intel's Official Guide to 386™ Computing, written by PC Computing's Editor -in-Chief Michael Edelhart, with chapters contributed by experts in the field and reviewed by Intel Corporation, has the inside information you've been looking for. Intel's Official Guide to 386™ Computing • Covers every aspect of what your 386 computer can do. • Discusses 386 microprocessor hardware, system software, and applications software. •Provides a guide to programming tools for 386 PC systems. •Spans the 386 PC family from the 386™ SX™ CPU notebook to the 33MHz 386™ DX CPU network server. Intel's Official Guide to 386™ Computing įs the best book to help you become more productive with your 386 computer." (Copied from the paste).
Foreword. Acknowledgments. Introduction. 1. What's so special about the 386 microprocessor? 2. The many flavors of 386 PCs. 3. Configuring a 386 system to match your needs. 4. Turning an older pc into a 386 CPU-based machine. 5. Getting the most from DOS ON A 386 PC. 6. Getting the most from Windows 3.0 on a 386 PC. 7. UNIX and 386 PC´s. 8. Getting the most from networks with the 386 chip. 9. Using DOS software on a 386 PC. 10. Making the transition from DOS to Windows 3.0. 11. 386 CPU-based software. 12. Getting the most from applications with UNIX on a 386 PCs. 13. Programming 386 PCs. 14. PCs of the nineties and beyond. A. Manufacturers of 386 CPU- based products. Glossary. Index.
Keywords: MICROPROCESSORS; INTEL -- MICROPROCESSOR; INTEL 80386 -- MICROPROCESSOR; 386 PC SYSTEMS; UNIX -- OPERATING SYSTEM